1971
DOI: 10.1063/1.1674756
|View full text |Cite
|
Sign up to set email alerts
|

The n-π* Absorption and Emission of Optically Active trans-β-Hydrindanone and trans-β-Thiohydrindanone

Abstract: The n-π* transitions (absorption, circular dichroism, luminescence, linear and circular polarization of luminescence) of trans-β-hydrindanone (I) and trans-β-thiohydrindanone (II) are discussed. The C2 symmetry of I and II is taken into account with the aid of expressions that are derived for nonrigid molecules having a twofold axis of symmetry. This allows the absorption of I to be split into a part due to transitions polarized along the twofold axis (z axis) and a part due to x, y-polarized vibration-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

1972
1972
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 22 publications
0
45
0
Order By: Relevance
“…In these experiments, the separated enantiomers of trans-β-hydrindanone and trans-β-thiohydrindanone were investigated, with results demonstrating the potential utility of CPL as a structural probe of emissive states. 15 Subsequent studies have demonstrated the observation of CPL for a variety of chiral molecules in solution, including organic systems, biomolecules and inorganic metal complexes. 16 Generally speaking, it is apparent from the literature that CPL phenomena are best exemplified by chiral lanthanide complexes.…”
Section: Systems Exhibiting Cplmentioning
confidence: 99%
“…In these experiments, the separated enantiomers of trans-β-hydrindanone and trans-β-thiohydrindanone were investigated, with results demonstrating the potential utility of CPL as a structural probe of emissive states. 15 Subsequent studies have demonstrated the observation of CPL for a variety of chiral molecules in solution, including organic systems, biomolecules and inorganic metal complexes. 16 Generally speaking, it is apparent from the literature that CPL phenomena are best exemplified by chiral lanthanide complexes.…”
Section: Systems Exhibiting Cplmentioning
confidence: 99%
“…The circular polarization of luminescence (CPL) of a chromophore is the emission analog of circular dichroism, and is related to the conformation of the electronically excited chromophore in the same way that circular dichroism is related to the conformation of the chromophore in the ground state (7)(8)(9)(10)(11)(12)(13). CPL is thus a manifestation of the chirality, or asymmetry, of the molecule in addition to circular dichroism and optical rotatory dispersion.…”
mentioning
confidence: 99%
“…2 is a reflection of the asymmetry induced in the TNS chromophore by the protein environment when the dye is in the excited state. If the conformation and environment of the chromophore in the excited state are the same as those in the ground state, and if the absorption and emission processes involve exactly the same pairs of quantum states, the emission anisotropy factor, ge, should be of the same sign and magnitude as the absorption anisotropy factor, ga (7,8,14). Obviously, the value of ge obtained for the chymotrypsin-TNS complex is markedly smaller, by about a factor of 10, than the value of gp obtained for this complex.…”
Section: Resultsmentioning
confidence: 99%
“…An absorption band is circularly dichroic if the relevant excitation involves both an electric and a magnetic transition dipole moment and if the two transition moments are not orthogonal in space (7). Analogously, when the above conditions are fulfilled for a radiative transition from an excited state to the ground state, i.e., in luminescence, the light emitted by the luminescent molecules in solution will be partly circularly polarized (7,8). If the absorption and emission processes involve exactly the same pairs of quantum states, the extent of circular dichroism (CD) and the degree of circular polarization of the luminescence are related to each other by a simple expression (see below).…”
mentioning
confidence: 99%